1999
DOI: 10.1055/s-1999-2753
|View full text |Cite
|
Sign up to set email alerts
|

The Suzuki-Miyaura Cross-Coupling Reactions of 6-Halopurines with Boronic Acids Leading to 6-Aryl- and 6-Alkenylpurines

Abstract: The Suzuki-Myiaura cross-coupling reactions of 9-benzyl-6-chloropurine with boronic acids gave 6-alkylated purines in moderate to excellent yields. The best results with electron rich arylboronic acids were obtained in toluene in the presence of anhydrous K 2 CO 3 as a base, while electron poor boronic acids and alkenyl boronic acids gave better results using aqueous K 2 CO 3 in DME. The reaction was successfully applied for the synthesis of 6-phenylpurine bases and nucleosides.Purine bases modified in the 6-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…A limited range of simple benzylamine and phenethylamine substituents were added to the purine core, aiming to access acidic residues in the ribose binding pocket. Suzuki couplings to the protected 6-chloropurine 3 17 attached either benzaldehyde (4,5) or (cyanomethyl)phenyl (8,9) groups, which were elaborated by reductive amination and reduction, respectively (Scheme 1). The increase in PKB enzyme inhibition seen for compounds such as 6 (pdb code 2UVY), 7, and 11 (Table 1) indicated that additional binding interactions were present, which was confirmed by crystallography with the chimera (Figure 1b).…”
mentioning
confidence: 99%
“…A limited range of simple benzylamine and phenethylamine substituents were added to the purine core, aiming to access acidic residues in the ribose binding pocket. Suzuki couplings to the protected 6-chloropurine 3 17 attached either benzaldehyde (4,5) or (cyanomethyl)phenyl (8,9) groups, which were elaborated by reductive amination and reduction, respectively (Scheme 1). The increase in PKB enzyme inhibition seen for compounds such as 6 (pdb code 2UVY), 7, and 11 (Table 1) indicated that additional binding interactions were present, which was confirmed by crystallography with the chimera (Figure 1b).…”
mentioning
confidence: 99%
“…[11] A similar reaction using n-butylboronic acid was described by Hocek and co-workers and by Echavarren and coworkers. [12][13][14] However, the coupling products were obtained in low yields. In order to enhance the yields of these reactions, Falck and co-workers examined other reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Suzuki crosscoupling reactions of 9-benzyl-6-chloropurine with boronic acids have recently been reported to provide 6-substituted purines in moderate to excellent yields (Eq. (46)) [77]. …”
Section: ð41þmentioning
confidence: 99%